Analisis Pengaruh Upah, Tingkat Pendidikan, Jenis Kelamin, Dan Usia Terhadap Produktifitas Tenaga Kerja Pada Sektor Industri Tenun Ikat Di Kota Kediri - Kartika Candra; Budi Heryanto; Sri Rochani (Fakultas Ekonomi Universitas Kadiri, 2019)
Productivity is one aspect of driving the progress of industry and economic growth. Increasing productivity to help the existing economic development in order to realize the common goal of equalizing the welfare of the community. Therefore, it is necessary to have good cooperation between the owner of the industry and the workforce in order to increase the productivity of the workforce in order to achieve equal distribution of the welfare of the community. The higher productivity of labor will increase industrial progress. But many factors can affect the high and low productivity of the workforce. Therefore what will be analyzed are: ‘wages, education level, gender, and age for labor productivity in the woven weaving industry sector in Kota Kediri. The purpose of this study was to determine the effect of ‘wages, education level, gender, and age on labor productivity in the woven weaving industry in Kota Kediri. This study uses questionnaires, documentation and direct interviews with 60 respondents in the ikat weaving industry in Kediri City. This research is quantitative research with SPSS analysis tools. The results of this study indicate the variables of wages, education level, gender and age on the productivity of